Brand strategy and content management on Instagram: scheduling and message length as factors to improve engagement (Communication & Society, 2022)
Companies use social media in their communication strategy to connect with their audiences via online brand communities and social media fan pages. In this context, the scientific community defines the term ‘engagement’ as the primary metric used to identify the degree to which brand and consumers are organically connected. This phenomenon gets measured by audience interactions with the brand content, which is the main factor stimulating participation and value perception in their relationship with the brand. Prior investigations show that the timing and duration of the messages published by the brand can predict the degree of social media engagement, however they do not provide the time and length patterns required for messages to increase engagement. For this purpose, we carried out a quantitative and descriptive content analysis of 14,067 Instagram posts from 14 Spanish brands across 10 industries. Findings allow us to conclude that brands are not fully optimising the scheduling of their timings during the working days and hours that drive the best level of interaction. Nonetheless, they do take advantage of the opportunity to publish longer messages to increase engagement. From a theorical and practical point of view, this analysis contributes to the understanding of the content factors that stimulate fan page engagement and provides guidelines for brand managers to efficiently define the content marketing strategy on Instagram.